Asylum Proceedings in the Czech Republic During the Migration Crisis - Černý, Petr (Journal of Legal Studies, 2020)
The article deals with the fundamental problems that emerged on the territory of the Czech Republic during the implementation of the asylum procedure throughout the migration crisis in the years 2015 to 2019. Problematic issues related primarily to the detention of migrant asylum seekers were identified by studying the key decisions of national and international courts. The first problematic point was the amendment to the Asylum Act, which required the courts to discontinue proceedings on the review of detention orders after the foreign national was released from detention. Due to the conflict with EU law and the impossibility to claim damages for unlawful detention, this amendment was finally annulledby the Constitutional Court. The second problem was that the factual conditions for asylum seekers in the EU Member State where the asylum seeker was to be transferred for the purpose of processing his/her asylum application, were not examined. In this regard, the situation had since been rectified and the administrative authorities and courts of the Czech Republic already take this aspect into account when deciding whether an asylum seeker detained on the territory of the Czech Republic is to be transferred to the country where he/she applied for asylum. The most serious problem is so far incomplete transposition of the Procedures Directive, in particular Article 46 of the Procedures Directive, which requires from the court to review the decisions on asylum in full jurisdiction and could possibly grant asylum itself. However, this requirement does not correspond to the concept and system of administrative courts in the Czech Republic and would require a significant and costly change. The last issue identified was the poor implementation of the Dublin III Regulation, involving not setting serious risk of absconding of an asylum seeker as a precondition forhis/her detention directly in the law.